The Moderating Effect of Location on Online Business Performance in the Philippines - Nathaniel Salcedo; Arthur Vincent Ballesteros; Marie Antoinette Rosete (Faculty of Science and Technology University of Pramita Indonesia, 2022)
It has been proven that business location greatly affects the performance of traditional businesses. The rise of online businesses was mainly due to their convenience in terms of location and customer proximity. The study aims to determine whether location serves as a moderating factor in the newer online businesses in terms of various determinants. With the prevalence of e-commerce, we would like to determine if these variables still play a factor in choosing an online business location as likewise with traditional businesses. This research demonstrates whether or not an online business location is correlated with business firm size, capital, and internet connection. The results indicate that location does in fact serve as a moderator in the relationship between firm size, starting capital, internet connectivity, and firm performance.